In situ structural modification of bacterial cellulose by sodium fluoride. (1st March 2020) - Sun, Bianjing; Zhang, Lei; Wei, Feng; AL-Ammari, Abdulrahman; Xu, Xuran; Li, Wenping; Chen, Chuntao; Lin, Jianbin; Zhang, Heng; Sun, Dongping
Graphical abstract: Highlights: The modification of BC structure is achieved in situ by fluoride. The concentration of fluoride has different effects on the micro-structures of BC. Fluoride treatment enhances the mechanical properties of BC. Abstract: Bacterial cellulose could be produced in any shape due to its high moldability during fermentation process, but structural modification often requires the inclusion of templates or other polymeric materials. In this work, sodium fluoride was introduced in bacterial cultivation process to modify the microstructure. Under static conditions, the final pH, BC yield, morphology, structure and properties of the obtained BC were investigated. Because of the stronger hydrogen bonding formed between fluoride and hydroxyl groups, majority of cellulose chains were no longer restricted and could not aggregate into wider cellulose ribbons. After the removal of fluoride, the cellulose chains undergo random rearrangement into bulky ribbon due to inter-fibril hydrogen bonding of hydroxyl groups, of which the crystallinity can remain as high as ∼60 % in dry state. The treatment of sodium fluoride led to different mechanical properties. The modification of BC structure can be easily achieved in situ by controlling NaF concentrations.